2015
DOI: 10.7314/apjcp.2015.16.4.1463
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Concurrent Chemoradiotherapy in Elderly Patients with Esophageal Squamous Cell Carcinoma: a Respective Study of 116 Cases from a Single Institution

Abstract: Background: To evaluate the safety and efficacy of combined chemoradiotherapy or radiotherapy alone in elderly patients with esophageal carcinoma to identify the best method of treatment. Materials and Methods: One hundred and sixteen patients with esophageal carcinoma aged 70 and older who received definitive radiotherapy or chemoradiotherapy entered the study. Overall survival (OS), disease-free survival (DFS) and treatmentrelated toxicities were assessed. Results: The median OS of the overall population was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Compared with patients treated with RT alone, patients who received CCRT had better survival outcomes (OS, 27.8 ± 2.4 vs 15.6 ± 1.9; PFS, 16.5 ± 1.9 vs 10.4 ± 0.9 months). Our results in elderly patients were consistent with those of previous studies, 15,17,18,24 but our study is the first to compare the efficacy of CCRT-1 and CCRT-2 in patients. However, the data failed to identify a statistically significant difference in median OS or median PFS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with patients treated with RT alone, patients who received CCRT had better survival outcomes (OS, 27.8 ± 2.4 vs 15.6 ± 1.9; PFS, 16.5 ± 1.9 vs 10.4 ± 0.9 months). Our results in elderly patients were consistent with those of previous studies, 15,17,18,24 but our study is the first to compare the efficacy of CCRT-1 and CCRT-2 in patients. However, the data failed to identify a statistically significant difference in median OS or median PFS.…”
Section: Discussionsupporting
confidence: 92%
“…13 The results of a phase II, single-arm study evaluating platinum-based chemotherapy combined with radiotherapy in patients older than 75 years with esophageal carcinoma suggested that chemotherapy is feasible and tolerable in elderly patients. 14 Meanwhile, there have been several retrospective studies [14][15][16][17][18][19][20][21][22][23][24] in elderly patients with OC had indicated that concurrent chemoradiation might be an optimal strategy for elderly patients with OC. Studies with more than 20 patients were listed in Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the results from propensity score and meta-analysis both showed survival advantage of IMRT for EC patients compared with traditional RT technique, such as 3D conformal RT (3D-CRT) [17,18]. Furthermore, on the basis of IMRT, definitive RT dose ≥60 Gy has yielded more favorable survival outcomes compared with standard dose 50.4 Gy in some latest researches [19,20], and the similar effect could be found in the elderly population without increasing treatment-related toxicities [21]. In the present study, all of very elderly patients were experienced IMRT and gained good short-term clinical effect, moreover, the subgroup of PGTV dose ≥ 60 Gy had superior LRFFS and better trends for OS (univariate analysis P = 0.055), these results indicated that dose escalation for tumor probably improve OS by enhancing LRFFS in very elderly EC patients, which also need to be further verified in prospective clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…However, to date, the appropriate doses and schedules of chemotherapy for these patients are yet to be determined [19]. Several studies had proven that dual-agent therapy achieved superior survival than single-agent CRT for elderly patients with ESCC [20,21]. Zhao et al demonstrated that CRT with a single agent in elderly patients had a similar survival benefit compared to CRT with a dual agent, accompanied by less toxicity [22].…”
Section: Discussionmentioning
confidence: 99%